2021
DOI: 10.1016/j.ebiom.2021.103548
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive metabolomics profiling reveals common metabolic alterations underlying the four major non-communicable diseases in treated HIV infection

Abstract: Background HIV infection and normal aging share immune and inflammatory changes that result in premature aging and non-communicable diseases (NCDs), but the exact pathophysiology is not yet uncovered. We identified the common metabolic pathways underlying various NCDs in treated HIV infection. Methods We performed untargeted metabolomics including 87 HIV-negative (–) normal controls (NCs), 87 HIV-positive (+) NCs, and 148 HIV+ subjects with only one type of NCDs, namely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Very recently, Ding et al conducted a case-control study using untargeted metabolomics to characterize the key metabolites and metabolic pathways associated with HIV infection and multiple NCDs, focusing on identifying the common metabolic pathways underlying them ( 64 ). They found that PLWH presented widespread alterations in cellular metabolism versus HIV-negative individuals, and glycerophospholipid metabolism emerged as the potential common metabolic pathway underlying NCDs in treated HIV infection; followed by d-glutamine and d-glutamate, and alanine, aspartate and glutamate metabolism.…”
Section: Systems Epidemiology Of Hiv/aidsmentioning
confidence: 99%
“…Very recently, Ding et al conducted a case-control study using untargeted metabolomics to characterize the key metabolites and metabolic pathways associated with HIV infection and multiple NCDs, focusing on identifying the common metabolic pathways underlying them ( 64 ). They found that PLWH presented widespread alterations in cellular metabolism versus HIV-negative individuals, and glycerophospholipid metabolism emerged as the potential common metabolic pathway underlying NCDs in treated HIV infection; followed by d-glutamine and d-glutamate, and alanine, aspartate and glutamate metabolism.…”
Section: Systems Epidemiology Of Hiv/aidsmentioning
confidence: 99%
“…HIV infection alters human cellular metabolism in many ways, favoring anabolic pathways, such as biosynthesis of nucleotides, phospholipids, cholesterol, amino acids, proteins, and glycoproteins, among others that are used for the assembly of newly synthesized viral particles. [1][2][3][4] Therefore, lipid, protein, and carbohydrate metabolism are expected to change greatly. 1 Additionally, antiretroviral therapy (ART) influences human metabolism by provoking side effects including metabolic syndrome which is characterized by increased abdominal fat, insulin resistance, type 2 diabetes, increased blood levels of free fatty acids, increased low-density lipoproteins (LDL), and verylow-density lipoproteins (VLDL), and, not rarely, premature aging.…”
Section: Introductionmentioning
confidence: 99%
“…4 It is also common to expect modified levels of glutamine, glutamate, and alanine-aspartateglutamate in HIV+ individuals. 7 Interesting metabolomic research on HIV/AIDS serum, and plasma, applying targeted or untargeted approaches 3,[7][8][9][10][11] had been published, with revealed changes in lipids, glucose, amino acids, choline, proteins, valine, and glutamine levels. 12 Glutamine plays many important metabolic roles, as a precursor of glutathione, purines, and glutamate.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to being related to maternal age hypertension, it is also associated with albumin levels. Pregnant women over 35 years of age will have lower albumin levels and experience an almost double increased risk of hypertension in primiparous and multipara (Ding et al, 2021). Moreover, young people less than 19 years old can also escalate the risk of low albumin levels (Deng et al, 2021).…”
Section: Resultsmentioning
confidence: 99%